The contents of uranium and thorium in the dominating kinds of plants of the Central Caucasus - T. A. Asvarova (Юг России: экология, развитие, 2015)
The result of this work have shown that the difference of contents uranium and thorium of various plants of Great Caucasus dependents views plants, on various types rock, type of soils and physicalchemicalproperties of soil. The maximum concentration of uranium and thorium are registered in Saxifraga mochata, S. Dinikii, S. exarata, S. carinata, and the minimum concentration is in Veratrum Lobelianum.